Associations between anterior knee pain and 2-year patellofemoral cartilage worsening: The MOST study - Lanois, C. J.; Collins, N.; Neogi, T.; Guermazi, A.; Roemer, Frank; LaValley, M.; Nevitt, M.; Torner, J.; Lewis, C. E.; Stefanik, J. J. (Osteoarthritis and Cartilage, 2023)
Objective: Anterior knee pain (AKP) is associated with patellofemoral osteoarthritis (PFOA), but longitudinal studies are lacking. If AKP precedes PFOA, it may create an opportunity to identify and intervene earlier in the disease process. The purpose of this study was to examine the longitudinal relation of AKP to worsening patellofemoral (PF) cartilage over two years. Design: Participants were recruited from the Multicenter Osteoarthritis Study, a longitudinal study of individuals with or at risk for knee osteoarthritis (OA). Exclusion criteria included bilateral knee replacements, arthritis other than OA, and radiographic PFOA. At baseline, participants completed a knee pain map questionnaire and underwent knee magnetic resonance imaging (MRI). Imaging was repeated at 2-year follow-up. Exposure was presence of frequent AKP. Outcome was worsening cartilage damage in the PF joint defined as increase in MRI Osteoarthritis Knee Score from baseline to 2 years. Log-binomial models were used to calculate risk ratios (RR). Results: One knee from 1083 participants (age 56.7 ± 6.6 years; body mass index 28.0 ± 4.9 kg/m2) was included. Frequent AKP and frequent isolated AKP were present at baseline in 14.5% and 3.6%, respectively. Frequent AKP was associated with an increased risk (RR: 1.78, 95% confidence interval: 1.21, 2.62) of 2-year worsening cartilage damage in the lateral PF compartment. No association was found between frequent AKP and worsening in the medial PF joint. Conclusion: Frequent AKP at baseline was associated with worsening cartilage damage in the lateral PF joint over 2 years.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Anterior knee pain; Patellofemoral cartilage; Patellofemoral OA